The Effectiveness of Educational Games in Digital Literacy to Improve Healthy Social Interactions in Elementary Schools - Putri, Dyta Anggraini; Wulandari, Murfiah Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to determine the effectiveness of educational games in fostering digital literacy to enhance healthy social interaction among elementary school students. By leveraging digital game-based learning, the research examines whether gamemediated activities can stimulate student engagement and promote constructive peer relationships. Methodology: Employing a quantitative quasi-experimental design with pretest–posttest control groups, the study involved two fifthgrade classes at an elementary school: class VA (experimental) and class VB (control). Both groups completed a pretest measuring healthy social interaction, after which the experimental group engaged in a series of educational game sessions while the control group followed regular instruction. A posttest was administered to both groups, and data were analyzed using the General Linear Model and normalized gain (N-gain) to assess learning effectiveness. Results: The experimental group (VA) achieved an N-gain of 79.16%, categorizing it as highly effective in improving healthy social interaction. In contrast, the control group (VB) recorded an N-gain of 30.79%, indicating a less effective outcome. These results demonstrate that students who learned via educational games exhibited significantly greater improvements in cooperative behaviors, communication skills, and mutual respect. Applications/Originality/Value: By confirming that educational game-based interventions can effectively cultivate healthy social interaction, this study provides a novel contribution to the literature on digital literacy and social skills development. Educators and curriculum designers can adopt game-centered modules to simultaneously build technological fluency and interpersonal competencies. Furthermore, the research highlights a previously underexplored linkage between educational gaming and social well-being, offering new directions for both pedagogical practice and future studies.